Modelling electric vehicles as an abatement technology in a hybrid CGE model - Stefan Schmelzer; Michael Miess; Milan Scasny; Vedunka Kopecna (Charles University in Prague, Institute of Economic Studies (IES), 2018)
We present a novel methodology to quantify the social costs and benefits (net social costs) of electric vehicles as an endogenous, demand-driven abatement technology in a general equilibrium framework. This new costing approach relates general equilibrium effects resulting from an increased market penetration of electric vehicles to the external environmental and health effects of the corresponding change in emissions. To this end, we develop a hybrid model combining a computable general equilibrium (CGE) with a discrete choice (DC) model that is capable of depicting an endogenous demand-driven uptake of alternative fuel vehicles. The discrete choice model of the consumer purchase decision between conventional, hybrid, plug-in hybrid, and electric vehicles is directly integrated into the CGE model. This hybrid CGE-DC model features a detailed accounting of vehicle eet development, including yearly numbers of vehicle purchases and cohort depreciation. It depicts nine households differentiated by the degree of urbanization and education, accounts for detailed consumer preferences for the purchase of a passenger vehicle and mode choice decisions. The hybrid CGE-DC model is additionally hard-linked to a bottom-up module for elektricity production by several technologies to provide input for an established impact pathway analysis to quantify the external costs relating to the changed composition of the vehicle eet and technologies to generate electricity. We apply this methodology to Austria as an empirical example, considering current measures and trends for the uptake of electric vehicles into the vehicle eet. In particular, we quantify the net social costs of additional measures to foster the introduction of electromobility that are part of the current policy discussion in Austria, and thus provide a blueprint for further application in different national contexts.
Keywords: C68; D12; D58; H22; H23; Q43; Q52; R42; 330; hybrid CGE model; discrete choice; electric vehicles; environmental benefits